Struggles in the Orthodox Jewish shidduch dating system—A large‐scale qualitative analysis. Issue 1 (23rd July 2022) - Rosenbach, Naomi; Sokol, Yosef; Rosensweig, Chayim; Bernstein, Devorah; Salamon, Michael J.; Schechter, Isaac
Abstract: Marriage is an important life goal and is highly valued among Orthodox Jews. Shidduch dating refers to the arranged dating system that is typically used within the community. Previous research and anecdotal evidence suggest that the shidduch system has become difficult and challenging for many individuals, yet there is a dearth of evidence on the subject. This study set out to explore issues related to dating and marriage within the Orthodox Jewish community using a large sample size. Participants included 889 Orthodox individuals across diverse demographic groups who responded to an optional question within a larger survey inquiring about their thoughts and experiences on the subject. An inductive qualitative analysis was conducted, and this paper focuses on the seven most prevalent themes that emerged. These themes include issues related to superficial criteria in mate selection, gender segregation, perceived surplus of females, pressure to marry before feeling ready, the formal structure of shidduch dating, the exclusion of specific groups from the process and lack of education in areas of intimacy and sexuality. This study is important in promoting clinical awareness regarding the struggles that many Orthodox Jewish daters face and underscores the need for communal change addressing these issues.